(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article outlines the tasks of forming and improving the professional competencies of future engineers in a digital educational environment in Uzbekistan and improving the professional competencies of engineers in a digital educational environment in technical higher educational institutions.